Characterization of an Arabidopsis Defensin-like Gene Conferring Resistance against Nematodes - Abdalmenem I. M. Hawamda; Susanne Reichert; Muhammad Amjad Ali; Muhammad Amjad Nawaz; Tina Austerlitz; Patricia Schekahn; Amjad Abbas; Raimund Tenhaken; Holger Bohlmann (Plants, 2022)
Arabidopsis contains 317 genes for defensin-like (DEFL) peptides. DEFLs have been grouped into different families based mainly on cysteine motifs. The DEFL0770 group contains seven genes, of which four are strongly expressed in roots. We found that the expression of these genes is downregulated in syncytia induced by the beet cyst nematode Heterodera schachtii as revealed by RNAseq analysis. We have studied one gene of this group, At3g59930, in detail. A promoter::GUS line revealed that the gene is only expressed in roots but not in other plant organs. Infection of the GUS line with larvae of H. schachtii showed a strong downregulation of GUS expression in infection sites as early as 1 dpi, confirming the RNAseq data. The At3g59930 peptide had only weak antimicrobial activity against Botrytis cinerea. Overexpression lines had no enhanced resistance against this fungus but were more resistant to H. schachtii infection. Our data indicate that At3g59930 is involved in resistance to nematodes which is probably not due to direct nematicidal activity.